The Effect of Adding Calcium Stearate on Wear-resistance of Ultra-high Molecular Weight Polyethylene. (2015) - Panin, С.V.; Kornienko, L.A.; Suan, T. Nguyen; Ivanova, L.R.; Poltaranin, M.A.
Abstract: In order to find an effective solid lubrication filler for the composites based on ultra-high molecular weight polyethylene, tribotechnical properties of UHMWPE and its blends with calcium stearate (С36Н70СаО4, CS) under dry friction, boundary lubrication and abrasion were studied. It is demonstrated that wear rate of UHMWPE-CS compositions under dry sliding friction decreases by more than 4 times as compared to pure UHMWPE while the mechanicals properties do not change substantially. Under abrasion conditions the wear rate of the stated composites rises with the increased content of the filler. The optimal filler weight fraction is determined in terms of ensuring maximum wear resistance. The wear mechanisms of UHMWPE-based polymer compounds with a solid lubrication filler under dry sliding friction conditions and abrasion are discussed.